Secondary battery and electronic device
By adopting a double-layer negative electrode design and specific solid-state electrolyte particles in secondary batteries, the shortcomings in the current secondary batteries in terms of rate discharge performance and cycling performance are solved, and better electrode dynamics and performance improvements are achieved.
Patent Information
- Application Number
- CN202411957777.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing secondary batteries have shortcomings in terms of rate discharge performance and cycle performance, especially while suppressing the expansion of the electrode sheet, it is difficult to improve both performances.
A double-layer negative electrode design is adopted, wherein the first material layer is silicon-based material and the second material layer is carbon-based material. Solid electrolyte particles containing specific elements are added to the two layers to improve the electron transfer rate and ion conduction efficiency and inhibit the expansion of the electrode sheet.
By optimizing the selection of the double-layer negative electrode structure and electrolyte material, the rate discharge performance and cycling performance of the secondary battery are significantly improved, while suppressing the expansion of the electrode sheet.
Smart Images

Figure BDA0005216648110000221 
Figure BDA0005216648110000231 
Figure BDA0005216648110000241
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to a secondary battery and an electronic device. Background Art
[0002] With the development of society, secondary batteries have become an indispensable energy storage and supply unit. From smartphones and wearable devices in people's daily lives to large-scale electric vehicles and distributed energy storage systems, the application scope of secondary batteries continues to expand and penetrate deeply. In these diverse application scenarios, the requirements for their performance are becoming more and more stringent, among which rate discharge performance and cycle performance are some of the key indicators to measure the quality and practicality of secondary batteries. Summary of the invention
[0003] The embodiments of the present application provide a secondary battery and an electronic device, which achieve better rate discharge performance and lower expansion rate while improving cycle performance.
[0004] In the first aspect, the embodiment of the present application provides a secondary battery, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte. The negative electrode plate includes a first material layer, a second material layer and a negative electrode current collector; the first material layer includes silicon-based particles and first particles, and the first particles include at least four of lithium, lanthanum, aluminum, titanium, phosphorus or oxygen; the second material layer includes carbon-based particles and second particles, and the second particles include lithium, lanthanum, zirconium and oxygen; the second material layer is arranged between the negative electrode current collector and the above-mentioned first material layer.
[0005] Based on the secondary battery of the embodiment of the present application, by adopting a double-layer negative electrode design, the first material layer is a silicon-based material, and the second material layer is a carbon-based material, the electron transfer rate can be improved and the volume expansion of the upper silicon material can be controlled. On this basis, the inventors found that the first material layer further includes solid electrolyte particles containing the above elements, which have reversible lithium insertion and extraction capacity, can react on the surface of the active material during the charge and discharge process to form a stable electronic ion conductor, inhibit the side reaction of silicon and the electrolyte, and improve the volume expansion of the silicon material; the second material layer further includes solid electrolyte particles containing the above elements, which have excellent stability, can improve the ion conduction efficiency of the second material layer, and cooperate with the first material layer to build an ion conduction network to improve the electrode dynamics. By optimizing the double-layer negative electrode structure and the selection of the electrolyte material therein in the above manner, it is possible to improve the rate discharge performance and cycle performance while inhibiting the expansion of the electrode.
[0006] In some embodiments, the circumscribed circle of the cross section of the silicon-based particles is a first circumscribed circle, the diameter of the first circumscribed circle is R1 nm, the circular region concentric with the first circumscribed circle and with a radius of R1+500 nm is the first region, the number of first particles in the first region is M, 10≤M≤119. Based on the secondary battery of the embodiment of the present application, by regulating the quantitative relationship between the silicon-based particles and the first particles in the first material layer within the above range, a suitable number of first particles are distributed on the surface of the silicon-based particles, so that it can not only construct an efficient ion conduction channel and reduce the solvation energy of the silicon material surface, but also form an in-situ protective layer to protect the reactivity of the silicon surface, thereby further slowing down the expansion rate of the silicon-based material and improving the electrode dynamics, thereby suppressing the expansion of the electrode while taking into account the improvement of rate discharge performance and cycle performance.
[0007] In some embodiments, the circumscribed circle of the cross section of the carbon-based particles is a second circumscribed circle, and the diameter of the second circumscribed circle is R2 nm; a circular area concentric with the second circumscribed circle and with a radius of R2+500nm is the second area, and the number of second particles in the second area is N, 4≤N≤88, preferably 11≤N≤38. Based on the secondary battery of the embodiment of the present application, by regulating the quantitative relationship between the carbon-based particles and the second particles in the second material layer within the above range, a suitable number of second particles are distributed on the surface of the carbon-based particles, which can further improve the ion conduction efficiency of the second material layer, cooperate with the first material layer to build an ion conduction network, and improve the electrode dynamics, thereby further suppressing the expansion of the electrode while taking into account the improvement of rate discharge performance and cycle performance.
[0008] In some embodiments, the secondary battery satisfies at least one of the following conditions: (1) the carbon-based particles include at least one of graphite or hard carbon; (2) the first particles include Li 1+x Al x Ti 2-x (PO4)3 or Li x La (2-x) / 3 TiO3, where 0.1≤x≤0.3; (3) the second particle includes Li7La3Zr2O2. Based on the secondary battery of the embodiment of the present application, the first particle includes lithium aluminum titanium phosphate with a NASICON structure or lithium lanthanum titanate with a perovskite structure, which has a reversible lithium deintercalation capacity and can react on the surface of the active material during the charge and discharge process to form a stable electronic ion conductor, reduce the side reaction between silicon and the electrolyte, and inhibit the volume expansion of the silicon material; the second particle includes lithium lanthanum zirconate with a garnet structure, which has excellent stability, can improve the ion conduction efficiency of the second material layer, and cooperate with the first material layer to construct an ion conduction network to enhance the electrode dynamics, thereby inhibiting the expansion of the electrode while improving the rate discharge performance and cycle performance.
[0009] In some embodiments, the first particle or / and the second particle further include a doping element, and the doping element includes at least one of niobium, zirconium, germanium, tantalum, lanthanum, sulfur, silicon or fluorine. Further adding the above doping elements to the solid electrolyte can improve the rate discharge performance and cycle performance while suppressing the expansion of the pole piece.
[0010] In some embodiments, based on the mass of the first material layer, the mass proportion of titanium is T%, 2.12×10 -3 ≤T≤1.36, preferably 0.14≤T≤0.54. Based on the secondary battery of the embodiment of the present application, by controlling the mass ratio of the titanium element in the first material layer within the above range, it is possible to further improve the rate discharge performance and cycle performance while suppressing the expansion of the electrode.
[0011] In some embodiments, based on the mass of the first material layer, the mass proportion of silicon is a%, the mass proportion of phosphorus is b%, and the first material layer satisfies at least one of the following conditions: (1) 5≤a≤98.6; (2) 0.04≤b≤2.43; (3) 2.06≤a / b≤2465. Based on the secondary battery of the embodiment of the present application, by controlling the mass relationship between silicon and phosphorus in the first material layer within the above range, it is possible to further suppress the expansion of the electrode while improving the rate discharge performance and cycle performance.
[0012] In some embodiments, the thickness of the first material layer is H1 μm, the thickness of the second material layer is H2 μm, p=H1 / (H1+H2), 0.08≤p≤0.86. Based on the secondary battery of the embodiment of the present application, by controlling the thickness relationship between the first material layer and the second material layer within the above range, the thickness of the first material layer and the second material layer is at a relative balance point, which can effectively control volume expansion without significantly affecting rate discharge performance and cycle performance.
[0013] In some embodiments, the first material layer and the second material layer both include a binder. Based on the mass of the negative electrode plate, the mass proportion of the binder in the first material layer is 1.2% to 12.8%, and the mass proportion of the binder in the second material layer is 0.5% to 2.2%. Based on the mass of the negative electrode plate, the mass proportion of the binder in the first material layer is K%, and the mass proportion of the binder in the second material layer is J%, 0.55≤K / J≤25.6, preferably 1.5≤K / J≤16. Based on the secondary battery of the embodiment of the present application, by controlling the mass ratio of the binder in the first material layer and the second material layer within the above range, the amount of binder in the first material layer and the second material layer can be within a suitable range, which can not only alleviate the volume expansion of the silicon material during the cycle, but also take into account the improvement of rate discharge performance and cycle life.
[0014] In some embodiments, the electrolyte includes fluoroethylene carbonate, and based on the mass of the electrolyte, the mass proportion of fluoroethylene carbonate is E%, 2.2≤E≤13.5, preferably 5.5≤E≤11.5. Based on the secondary battery of the embodiment of the present application, the electrolyte includes fluoroethylene carbonate, which can form a LiF-rich SEI during the battery cell cycle, which can improve the ion transmission speed in the pole piece on the one hand, and reduce the side reactions during the pole piece cycle on the other hand, thereby further suppressing the expansion of the pole piece while improving the rate discharge performance and cycle performance.
[0015] In some embodiments, the electrolyte includes lithium nitrate. Based on the mass of the electrolyte, the mass proportion of lithium nitrate is F%, 0.1≤F≤8.8. Based on the secondary battery of the embodiment of the present application, the electrolyte includes lithium nitrate, which can form a Li3N-rich SEI during the battery cell cycle. Li3N has extremely high ion conductivity and can accelerate lithium ion conduction, thereby further suppressing the expansion of the electrode while improving the rate discharge performance and cycle performance.
[0016] In some embodiments, both the positive electrode sheet and the negative electrode sheet are provided with a tab; the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence and then wound to form an electrode assembly, with the thickness direction of the electrode assembly as the first direction; the negative electrode sheet is provided with a first adhesive tape and a second adhesive tape, and the positive electrode sheet is provided with a third adhesive tape; the first adhesive tape is provided on at least part of the surface of the negative electrode tab, and the third adhesive tape is provided on at least part of the surface of the positive electrode tab; the projection of the second adhesive tape along the first direction overlaps at least part of the projection of the positive electrode tab along the first direction. Based on the secondary battery of the embodiment of the present application, by providing the above-mentioned second adhesive tape, on the one hand, it can protect against short circuits caused by the positive electrode tab piercing the separator, and on the other hand, it can improve the problem of reduced cohesion of the electrode sheet caused by the large difference in specific surface area of the material particles in the negative electrode material layer and the uneven adsorption force on the binder, thereby further suppressing the expansion of the electrode sheet while taking into account the improvement of rate discharge performance and cycle performance.
[0017] In some embodiments, the area of the second adhesive tape is S1 cm 2 , the area of the first material layer is S2 cm 2 , S=S1 / S2, 0.3≤S≤6. Based on the secondary battery of the embodiment of the present application, by controlling the ratio of the area of the second adhesive tape to the area of the first material layer within the above range, the problem of reduced cohesion of the electrode sheet due to the large specific surface area of the particles added to the negative electrode material layer and the strong adsorption force to the binder can be further improved, thereby further suppressing the expansion of the electrode sheet while improving the rate discharge performance and cycle performance.
[0018] In some embodiments, the capacitance-voltage characteristic curve of the negative electrode plate has reduction peaks at 0 to 0.8 V, 1.5 V to 1.8 V, and 2.3 V to 2.5 V. Based on the secondary battery of the embodiment of the present application, when its capacitance-voltage characteristic curve includes a characteristic peak in a specific voltage interval, the secondary battery has a lower electrode expansion rate and better rate discharge performance and cycle performance.
[0019] In a second aspect, an embodiment of the present application provides an electronic device, which includes the secondary battery mentioned above. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.
[0021] A first aspect of an embodiment of the present application provides a secondary battery, including a negative electrode, a positive electrode, an electrolyte and a separator.
[0022] negative electrode
[0023] The negative electrode includes a negative electrode plate, and the negative electrode plate includes a first material layer, a second material layer and a negative electrode current collector. The first material layer includes silicon-based particles and first particles, and the first particles include at least 4 of lithium, lanthanum, aluminum, titanium, phosphorus or oxygen. The second material layer includes carbon-based particles and second particles, and the second particles include lithium, lanthanum, zirconium, titanium and oxygen. The second material layer is arranged between the negative electrode current collector and the first material layer. In some embodiments, the second material layer completely overlaps with the first material layer. In some embodiments, the second material layer and the first material layer partially overlap, for example, the edge of the second material layer may exceed the first material layer, or the edge of the first material layer may exceed the second material layer. The first material layer and the second material layer of the double-layer negative electrode design respectively include solid electrolyte particles containing the above elements, which can improve the dynamics of the electrode plate and improve the volume expansion of the silicon material, thereby suppressing the expansion of the electrode plate while improving the rate discharge performance and cycle performance.
[0024] In some of the embodiments, the circumscribed circle of the cross section of the silicon-based particles is a first circumscribed circle, the diameter of the first circumscribed circle is R1 nm, the circular region concentric with the first circumscribed circle and with a radius of R1+500nm is the first region, and the number of first particles in the first region is M, 10≤M≤119. For example, the number of first particles in the first region can be 10, 27, 53, 58, 94, 111, 119 or a value in the range of any two of these values. The quantitative relationship between the silicon-based particles and the first particles in the first material layer is regulated within the above range, so that an efficient ion conduction channel can be constructed, the solvation energy of the silicon material surface can be reduced, and an in-situ protective layer can be formed to protect the reactivity of the silicon surface, so as to further suppress the expansion of the electrode while taking into account the improvement of rate discharge performance and cycle performance.
[0025] In some of the embodiments, the circumscribed circle of the cross section of the above-mentioned carbon-based particles is a second circumscribed circle, and the diameter of the second circumscribed circle is R2 nm; a circular area concentric with the second circumscribed circle and with a radius of R2+500nm is the second area, and the number of second particles in the second area is N, 4≤N≤88, preferably 11≤N≤38. For example, the number of second particles in the second area can be 4, 11, 17, 32, 35, 48, 67, 88 or a value in the range composed of any two of these values. The quantitative relationship between the carbon-based particles and the second particles in the second material layer is regulated within the above range, and a suitable number of second particles are distributed on the surface of the carbon-based particles, which can further improve the ion conduction efficiency of the second material layer, cooperate with the first material layer to construct an ion conduction network, and enhance the electrode dynamics, thereby further suppressing the expansion of the electrode while taking into account the improvement of rate discharge performance and cycle performance.
[0026] In some embodiments, the secondary battery satisfies at least one of the following conditions: (1) the carbon-based particles include at least one of graphite or hard carbon; (2) the first particles include Li 1+x Al x Ti 2-x (PO4)3 or Li x La (2-x) / 3 TiO3, wherein 0.1≤x≤0.3; (3) the second particle comprises Li7La3Zr2O2. The first particle comprises lithium aluminum titanium phosphate with a NASICON structure or lithium lanthanum titanate with a perovskite structure, and the second particle comprises lithium lanthanum zirconate with a garnet structure, which can improve the rate discharge performance and cycle performance while suppressing the expansion of the electrode.
[0027] In some embodiments, the first particle or / and the second particle further include a doping element, and the doping element includes at least one of niobium, zirconium, germanium, tantalum, lanthanum, sulfur, silicon or fluorine. Further adding doping elements to the solid electrolyte can improve the rate discharge performance and cycle performance while suppressing the expansion of the pole piece.
[0028] In some embodiments, based on the mass of the first material layer, the mass proportion of titanium is T%, 2.12×10 -3 ≤T≤1.36, preferably 0.14≤T≤0.54. For example, the mass percentage of the titanium element in the first material layer can be 0.00212, 0.14, 0.35, 0.45, 0.54, 0.58, 0.62, 0.78, 1.36 or a value in the range formed by any two of these values. The mass percentage of the titanium element in the first material layer is controlled within the above range, which can further improve the rate discharge performance and cycle performance while suppressing the expansion of the electrode sheet.
[0029] In some embodiments, based on the mass of the first material layer, the mass percentage of silicon is a%, the mass percentage of phosphorus is b%, and the first material layer satisfies at least one of the following conditions: (1) 5≤a≤98.6; (2) 0.04≤b≤2.43; (3) 2.06≤a / b≤2465. For example, the mass percentage of silicon in the first material layer can be 5, 12.3, 37.6, 50.7, 55.0, 67.6, 87.7, 98.6, or a value within a range consisting of any two of these values. For example, the mass percentage of phosphorus in the first material layer can be 0.04, 0.05, 0.76, 1.39, 1.55, 1.60, 1.66, 2.36, 2.43, or a value within a range consisting of any two of these values. For example, the ratio of the mass proportion of silicon element to the mass proportion of phosphorus element in the first material layer can be 2.06, 23.50, 32.71, 48.63, 160.73, 671.04, 1012.29, 1425.59, 1624.76, 1989.97, 2465 or a value in the range formed by any two of these values. The mass relationship between silicon element and phosphorus element in the first material layer is controlled within the above range, which can further improve the rate discharge performance and cycle performance while suppressing the expansion of the electrode sheet.
[0030] In some embodiments, the thickness of the first material layer is H1 μm, the thickness of the second material layer is H2 μm, p=H1 / (H1+H2), 0.08≤p≤0.86. For example, the value of p can be 0.08, 0.21, 0.34, 0.48, 0.50, 0.67, 0.77, 0.86 or a value in the range formed by any two of these values. The thickness relationship between the first material layer and the second material layer is controlled within the above range, so that the thickness of the first material layer and the second material layer is at a relative balance point, which can effectively control the volume expansion without significantly affecting the rate discharge performance and cycle performance.
[0031] In some embodiments, the first material layer and the second material layer both include a binder. Based on the mass of the negative electrode sheet, the mass proportion of the binder in the first material layer is 1.2% to 12.8%. For example, the mass proportion of the binder in the first material layer can be 1.2%, 2.1%, 3.5%, 5.4%, 7.6%, 12.8%, or a value in the range of any two of these values. The mass proportion of the binder in the second material layer is 0.5% to 2.2%. For example, the mass proportion of the binder in the second material layer can be 0.5%, 0.71%, 1.2%, 1.4%, 1.5%, 1.7%, 2.2%, or a value in the range of any two of these values. Based on the mass of the negative electrode sheet, the mass proportion of the binder in the first material layer is K%, and the mass proportion of the binder in the second material layer is J%, 0.55≤K / J≤25.6, preferably 1.5≤K / J≤16. For example, based on the mass of the negative electrode sheet, the ratio of the mass proportion of the binder in the first material layer to the mass proportion of the binder in the second material layer can be 0.55, 0.76, 1.50, 7.0, 8.40, 10.50, 11.20, 12.30, 13.50, 16.00, 18.14, 25.60 or a value within the range formed by any two of these values. In some embodiments, the binder in the first material layer includes polyacrylic acid, and the binder in the second material layer includes styrene-butadiene rubber or carboxymethyl cellulose. The mass ratio of the binder in the first material layer and the second material layer is controlled within the above range, so that the amount of the binder in the first material layer and the second material layer is in a suitable range, which can not only alleviate the volume expansion of the silicon material during the cycle, but also take into account the improvement of the rate discharge performance and the improvement of the cycle life.
[0032] The negative electrode material layer of the present application also includes a conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent can be at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene, and the above-mentioned carbon nanotubes can include but are not limited to at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes.
[0033] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode material layer is 30μm to 160μm. In the present application, the negative electrode mixture layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. This application has no special restrictions as long as the purpose of this application can be achieved.
[0034] The present application has no particular restrictions on the compaction density of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 Up to 1.85g / cm 3 The present application has no particular limitation on the cold pressing pressure of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the cold pressing pressure of the negative electrode sheet can be 3 tons to 30 tons.
[0035] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the thickness of the conductive layer, as long as the purpose of the present application can be achieved, for example, the thickness of the conductive layer is 1μm to 10μm.
[0036] positive electrode
[0037] The positive electrode includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector. The positive electrode material layer includes a lithium-containing transition metal composite oxide, and the lithium-containing transition metal composite oxide includes Li w Na z Co 1-y A yO2, wherein 0.6<w<0.95, 0≤y<0.15, 0<z≤0.03, A is at least one selected from the group consisting of Al, Mg, Ti, Mn, Fe, Ni, Zn, Cu, Nb, Cr and Zr. For example, the above subscripts may be 0.6<w<0.7, 0≤y<0.10, and 0<z<0.01; 0.7<w<0.8, 0.05<y<0.10, and 0<z<0.02; 0.8<w<0.9, 0.06<y<0.09, and 0<z≤0.03; 0.9<w<0.95, 0.07<y<0.08, and 0.01<z<0.02; 0.6<w<0.9, 0.08<y<0.15, and 0.01<z≤0.03. By adding the above-mentioned lithium-containing transition metal composite oxide to the positive electrode material layer in the electrochemical device, and controlling the content ratio of each metal atom in the lithium-containing transition metal composite oxide, especially controlling the content ratio of sodium atoms to meet the above-mentioned range, it is possible to improve both the high-temperature storage performance and the low-temperature discharge performance of the electrochemical device.
[0038] In some embodiments, the positive electrode material layer includes a positive electrode conductive material. The type of positive electrode conductive material is not limited, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials can be used alone or in any combination.
[0039] In some embodiments, the positive electrode material layer includes a positive electrode binder. The type of the positive electrode binder is not particularly limited, and in the case of a coating method, any material that can be dissolved or dispersed in a liquid medium used in electrode manufacturing can be used. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, etc.; rubber polymers such as styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, etc.; thermoplastic elastomer polymers such as styrene-butadiene-styrene block copolymers or their hydrides, ethylene-propylene-diene terpolymers, styrene-ethylene-butadiene-ethylene copolymers, styrene-isoprene-styrene block copolymers or their hydrides; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, propylene-α-olefin copolymers; fluorine polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene-ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions, etc. The above positive electrode binders may be used alone or in any combination.
[0040] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as needed. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, a mixed medium of alcohol and water or water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran; amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.
[0041] Thickeners are generally used to adjust the viscosity of the slurry. In the case of using an aqueous medium, the thickener and styrene-butadiene rubber emulsion can be used for slurrying. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.
[0042] The type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.
[0043] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode material layer, the surface of the positive electrode current collector may include a conductive additive or a conductive coating. Examples of conductive additives may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of conductive coatings may include a mixture layer containing an inorganic oxide, a conductive agent, and a binder.
[0044] Electrolyte
[0045] The electrolytic solution used in the secondary battery of the present application includes an electrolyte and a non-aqueous solvent that dissolves the electrolyte.
[0046] In some embodiments, the electrolyte includes fluoroethylene carbonate. Based on the mass of the electrolyte, the mass proportion of fluoroethylene carbonate is E%, 2.2≤E≤13.5, preferably 5.5≤E≤11.5. For example, the mass proportion of fluoroethylene carbonate in the electrolyte can be 2.2, 3.7, 5.5, 6.1, 7.8, 8.3, 9.9, 11.5, 13.5 or a value within the range composed of any two of these values. Including fluoroethylene carbonate in the electrolyte can form a LiF-rich SEI during the battery cell cycle. On the one hand, it can increase the ion transfer rate in the electrode, and on the other hand, it can reduce the side reactions during the electrode cycle, thereby improving the rate discharge performance while improving the cycle performance.
[0047] In some embodiments, the electrolyte includes lithium nitrate. Based on the mass of the electrolyte, the mass percentage of lithium nitrate is F%, 0.1≤F≤8.8. For example, the mass percentage of lithium nitrate in the electrolyte can be 0.1, 0.7, 1.6, 3.4, 4.6, 7.3, 8.8 or a value within the range composed of any two of these values. The electrolyte includes lithium nitrate, which can form a Li3N-rich SEI during the battery cell cycle. Li3N has extremely high ion conductivity characteristics, which can accelerate lithium ion conduction, thereby further improving the rate discharge performance while improving the cycle performance.
[0048] The present application does not particularly limit the type of lithium salt, as long as the purpose of the present application can be achieved, for example, the lithium salt may include but is not limited to lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium trifluoromethanesulfonyl imide (LiTFSI), lithium bis (fluorosulfonyl) imide (LiFSI), lithium bis oxalate borate (LiBOB) or lithium difluoro oxalate borate (LiDFOB) at least one. Based on the mass of the electrolyte, the mass proportion of the lithium salt can be 8% to 15%, for example, the mass proportion of the lithium salt can be 8%, 9%, 10%, 11%, 12.5%, 13%, 15% or a range composed of any two of the values. The present application does not particularly limit the type of the above-mentioned non-aqueous solvent, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds or cyclic carbonate compounds. The above-mentioned linear carbonate compound may include but is not limited to at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate or ethyl methyl carbonate. The above-mentioned cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate, propylene carbonate, butylene carbonate or ethylene ethylene carbonate. The above-mentioned carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of ethylene glycol dimethyl ether, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.
[0049] Diaphragm
[0050] In the present application, a diaphragm is usually provided between the positive electrode and the negative electrode, and the diaphragm is used to separate the positive electrode plate and the negative electrode plate to prevent internal short circuit of the secondary battery, allow electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process.
[0051] The present application has no particular restrictions on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of the separator may include at least one of woven membrane, non-woven membrane, microporous membrane, composite membrane, rolled membrane or spun membrane.
[0052] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it may be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).
[0053] The pore size of the diaphragm in the present application is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In some embodiments, the thickness of the diaphragm is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the diaphragm is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the diaphragm is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the secondary battery can be ensured.
[0054] In some embodiments, both the positive electrode sheet and the negative electrode sheet are provided with a pole ear. The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence and then wound to form an electrode assembly, with the thickness direction of the electrode assembly as the first direction. The negative electrode sheet is provided with a first adhesive tape and a second adhesive tape, and the positive electrode sheet is provided with a third adhesive tape. The first adhesive tape is provided on at least a portion of the surface of the negative electrode ear, and the third adhesive tape is provided on at least a portion of the surface of the positive electrode ear. The projection of the second adhesive tape along the first direction overlaps at least partially with the projection of the positive electrode ear along the first direction. On the one hand, the second adhesive tape can protect against short circuits caused by the positive electrode ear piercing the separator, and on the other hand, it can improve the problem of reduced cohesion of the electrode sheet caused by the large difference in specific surface area of the material particles in the negative electrode material layer and the uneven adsorption force of the binder, thereby further suppressing the expansion of the electrode sheet while taking into account the improvement of rate discharge performance and cycle performance.
[0055] In some embodiments, the area of the second adhesive tape is S1 cm 2 , the area of the first material layer is S2 cm 2 , S=S1 / S2, 0.3≤S≤6. For example, the ratio of the area of the second adhesive tape to the area of the first material layer can be 0.3, 0.5, 1.3, 2.8, 3.5, 4.9, 6.0 or a value in the range formed by any two of these values. Controlling the ratio of the area of the second adhesive tape to the area of the first material layer within the above range can further improve the problem of reduced cohesion of the electrode sheet due to the large specific surface area of the particles added to the negative electrode material layer and the strong adsorption force on the binder, thereby further suppressing the expansion of the electrode sheet while improving the rate discharge performance and cycle performance.
[0056] In some embodiments, the capacitance-voltage characteristic curve of the negative electrode plate has reduction peaks at 0 to 0.8 V, 1.5 V to 1.8 V, and 2.3 V to 2.5 V. When the capacitance-voltage characteristic curve of the secondary battery contains the above characteristic peaks in a specific voltage range, the secondary battery has a lower electrode expansion rate and better rate discharge performance and cycle performance.
[0057] The present application also provides an electronic device, which includes the secondary battery of the present application. The electronic device includes but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini CD, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0058] Example
[0059] Hereinafter, taking lithium-ion batteries as an example, examples and comparative examples are given to more specifically describe the implementation of the secondary battery of the present application. Those skilled in the art will understand that the preparation method described in the present application is only an example, and any other suitable preparation method is within the scope of the present application. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0060] Example 1-1
[0061] 1. Preparation of positive electrode
[0062] The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 95:2:3, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm, and dried to obtain a positive electrode sheet coated with a positive electrode mixture layer on one side. Repeat the above steps on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a positive electrode mixture layer on both sides. By adjusting the pressure of the cold pressing, positive electrode sheets with different compaction densities and surface roughness can be obtained. After cold pressing, striping, and welding of the pole ears, a third adhesive tape is pasted on the surface of the pole ears, and dried to obtain a positive electrode sheet with a specification of 74mm×867mm.
[0063] 2. Preparation of electrolyte
[0064] In a dry argon atmosphere glove box, diethyl carbonate was used as a base solvent, lithium hexafluorophosphate (LiPF6) was dissolved in the base solvent, and vinylene carbonate and fluoroethylene carbonate were added to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass proportion of LiPF6 was 12.5%, the mass proportion of vinylene carbonate was 2%, and the mass proportion of fluoroethylene carbonate was 7%.
[0065] 3. Preparation of negative electrode
[0066] <Preparation of negative electrode sheet>
[0067] (1) Mix silicon-carbon material (mass ratio of silicon:carbon = 65:35) and graphite in a mass ratio of 8:92 to obtain negative electrode active material II; mix negative electrode active material II, polyacrylonitrile (PAA), carbon nanotubes (CNT), and second particles Li7La3Zr2O2 in a mass ratio of 97.99:1.2:0.8:0.01, then add deionized water and stir evenly to prepare a second slurry with a solid content of 45wt%. The second slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm to obtain a negative electrode sheet coated with a second material layer on one side; repeat the above steps on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a second material layer on both sides;
[0068] (2) mixing a silicon-carbon material (mass ratio of silicon to carbon = 65:35) and graphite in a mass ratio of 8:92 to obtain a negative electrode active material 1; mixing the negative electrode active material 1, polyacrylonitrile (PAA), carbon nanotubes (CNT), and the first particle Li 1.1 Al 0.1 Ti 1.9 (PO4)3 is mixed in a mass ratio of 97.99:1.2:0.8:0.01, and then deionized water is added and stirred to form a first slurry with a solid content of 45wt%. The first slurry is evenly coated on one surface of the negative electrode obtained in step (1); the above steps are repeated on the other surface of the negative electrode to obtain a negative electrode coated with the first material layer and the second material layer on both sides;
[0069] (3) After cold pressing, stripping, and welding of the tabs, a first adhesive tape is pasted on the surface of the tabs and dried to obtain a negative electrode sheet with a specification of 76.6 mm×875 mm.
[0070] 4. Preparation of diaphragm
[0071] A porous polyethylene film with a thickness of 15 μm was used as the separator.
[0072] 5. Preparation of lithium-ion batteries
[0073] Stack the positive electrode sheet, negative electrode sheet and separator in order, place the separator between the positive electrode sheet and the negative electrode sheet to play a role of isolation, stick the second adhesive tape on the negative electrode sheet, and wind it to obtain the electrode assembly. After winding, the projection of the second adhesive tape along the thickness direction of the electrode assembly overlaps with the projection of the positive electrode ear along the thickness direction of the electrode assembly. Place the electrode assembly in a packaging bag, remove moisture at 80°C, inject the above-mentioned electrolyte and package it. After the process of formation hot pressing, degassing, trimming and other processes, a lithium-ion battery is obtained.
[0074] 6. Test methods
[0075] (1) Particle number measurement
[0076] Take a lithium-ion battery, polish the negative electrode plate with argon ions and cut it open to expose the cross section of the plate along the thickness direction, and then use a scanning electron microscope to observe the cross section of the material particles in the cross section of the plate. The circle with the diameter of the two farthest points on the particle cross section is the circumscribed circle of the particle, and its radius is Rnm. The circular area concentric with the circumscribed circle and with a radius of R+500nm is the counting area. When counting, if only part of the cross section of a particle is located in the counting area, it is counted as one particle. Take the arithmetic mean of the counting results of 20 counting areas as the number of first particles in the first area or the number of second particles in the second area.
[0077] (2) Element content test
[0078] Take a lithium-ion battery, discharge it at a constant current of 0.5C to 2.8V to obtain a fully discharged battery, remove the negative electrode plate, analyze the cross-section of the plate along the thickness direction using energy dispersive X-rays, and test the mass proportions of titanium, silicon and phosphorus in the first material layer respectively.
[0079] (3) Test method for binder mass ratio
[0080] Take a lithium-ion battery, cut the negative electrode plate after ion polishing, so that the entire cross-section of the plate along the thickness direction is exposed, and then use an infrared spectrometer (ATR IR spectrum) to test the absorption spectrum of the cross-section, analyze the binder distribution pattern along the thickness direction of the electrode to obtain the relative content of the binder in the first material layer and the relative content of the binder in the second material layer, and divide the two relative contents to obtain the mass proportion of the binder.
[0081] (4) Capacitor-voltage characteristic curve test
[0082] For the initial first particles, the first particles were uniformly mixed with PVDF and carbon in a mass ratio of 8:1:1, and then coated on the current collector to prepare a pole piece. The prepared pole piece and the Li sheet were assembled into a button battery, which was charged and discharged at 0.2C, and the QV curve was integrated to obtain a dQ / dV-V image; for the secondary battery, a lithium-ion battery was taken, charged and discharged at 0.2C, and the QV curve was integrated to obtain a dQ / dV-V image.
[0083] (5) Thickness expansion performance test
[0084] Take the lithium-ion battery, place it in a constant temperature environment of 25℃, and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it to 4.5V at a constant current of 0.5C, and then charge it to a current of 0.025C at a constant voltage of 4.5V. Use a PPG soft-pack battery thickness gauge to test the battery thickness at a pressure of 700g, select 5 different points at the non-ear position to measure the thickness, record the thickness of the lithium-ion battery measured 5 times, and record the average of the 5 test values as the initial thickness. After the measurement is completed, discharge it to 3.0V at a constant current of 0.5C, let it stand for 5 minutes, charge it to 4.5V at a constant current of 0.5C, and then charge it to a current of 0.025C at a constant voltage of 4.5V. Repeat this step for 100 times, take out the battery, select 5 different points at the non-ear position, use a PPG soft-pack battery thickness gauge to test and record the battery thickness after the cycle at a pressure of 700g, and record the average of the 5 test values as the final thickness. Cyclic thickness expansion rate % = (final thickness - initial thickness) / initial thickness × 100%.
[0085] (6) 4C rate discharge test
[0086] Take a lithium-ion battery, charge it to 4.5V at 0.2C rate constant current at 25℃, then charge it to 0.05C at constant voltage, then let it stand for 30 minutes, then discharge it to 2.8V at 0.2C rate constant current, and test the lithium-ion battery 25℃ 0.2C rate discharge capacity; at 25℃, charge the lithium-ion battery to 4.5V at 0.2C rate constant current, then charge it to 0.05C at constant voltage, then discharge it to 2.8V at 4C rate constant current, and test the lithium-ion battery 4C rate discharge capacity. 4C rate discharge capacity retention rate % = 4C rate discharge capacity / 0.2C rate discharge capacity × 100%.
[0087] (7) Normal temperature cycle performance test
[0088] Take a lithium-ion battery and place it in a 25℃ constant temperature test box. Let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it to 4.5V at a constant current of 0.5C, then charge it to a current of 0.025C at a constant voltage of 4.5V, let it stand for 5 minutes, and discharge it to 2.8V at a constant current of 0.5C. Record it as the initial discharge capacity C0. Repeat this step for 500 cycles, record the discharge capacity C1 after 100 cycles, and calculate the cycle capacity retention rate of the lithium-ion battery. Cycle capacity retention rate % = C1 / C0×100%.
[0089] The lithium-ion batteries of the following embodiments or comparative examples differ from those of embodiment 1-1 only in that the amount of silicon-based particles and first particles in the first material layer, the amount of carbon-based particles and second particles in the second material layer, and the ratio of elements in the first particles are adjusted according to Table 1. The performance test results of the lithium-ion batteries of the embodiments and comparative examples are shown in Table 1 below.
[0090] Table 1
[0091]
[0092]
[0093] *In the above table, the calculation result of a / b is rounded to two decimal places.
[0094] As can be seen from Table 1, the lithium-ion batteries prepared in the embodiments of the present application have significantly improved energy densities for the lithium-ion batteries of Examples 1-1 to 1-26 relative to Comparative Example 1 in which the first material layer is not provided. Relative to Comparative Example 2 in which the first material layer does not contain the first particles, the energy density of the lithium-ion batteries of Examples 1-1 to 1-26 is significantly improved. Relative to Comparative Example 3 in which the second material layer is not provided, the rate discharge capacity retention performance, normal temperature cycle capacity retention performance, and cycle thickness expansion performance of the lithium-ion batteries of Examples 1-1 to 1-26 are significantly improved. Relative to Comparative Example 4 in which the second material layer does not contain the second particles, the rate discharge capacity retention performance, normal temperature cycle capacity retention performance, and cycle thickness expansion performance of the lithium-ion batteries of Examples 1-1 to 1-26 are significantly improved.
[0095] In particular, the lithium-ion battery prepared in the embodiment of the present application, when the number of first particles in the first region satisfies 10≤M≤119, the lithium-ion battery has excellent rate discharge capacity retention performance, room temperature cycle capacity retention performance, cycle thickness expansion performance and energy density. When the number of second particles N in the second region satisfies 4≤N≤88, especially 11≤N≤38, the lithium-ion battery has excellent rate discharge capacity retention performance, room temperature cycle capacity retention performance, cycle thickness expansion performance and energy density. When the mass proportion of titanium in the first material layer satisfies 2.12×10 -3 ≤T≤1.36, especially 0.14≤T≤0.54, the lithium-ion battery has excellent rate discharge capacity retention performance, room temperature cycle capacity retention performance, cycle thickness expansion performance and energy density. When the mass proportion of silicon in the first material layer satisfies 5≤a≤98.6, or the mass proportion of phosphorus in the first material layer satisfies 0.04≤b≤2.43, or the relationship between a and b satisfies 2.06≤a / b≤2465, the lithium-ion battery has excellent rate discharge capacity retention performance, room temperature cycle capacity retention performance, cycle thickness expansion performance and energy density.
[0096] The lithium-ion batteries of the following Examples 2-1 to 2-30 differ from those of Example 1-24 only in that the thickness of the first material layer and the second material layer, the mass proportion of the adhesive in the first material layer and the second material layer, the area ratio of the first adhesive tape, the second adhesive tape and the first material layer, and the mass proportion of fluoroethylene carbonate and lithium nitrate in the electrolyte are adjusted according to Table 2.
[0097] Table 2
[0098]
[0099]
[0100] *In the above table, the calculation results of p and K / J are rounded to two decimal places; the calculation result of S is rounded to one decimal place.
[0101] It can be seen from Table 2 that the lithium-ion battery prepared in the embodiment of the present application, when the thickness of the first material layer and the thickness of the second material layer are adjusted to meet 0.08≤p≤0.86, the rate discharge capacity retention performance, room temperature cycle capacity retention performance, cycle thickness expansion performance and energy density of the lithium-ion battery are better. When the mass ratio of the binder in the first material layer and the mass ratio of the binder in the second material layer are adjusted to meet 0.55≤K / J≤25.6, especially 1.5≤K / J≤16, the rate discharge capacity retention performance, room temperature cycle capacity retention performance, cycle thickness expansion performance and energy density of the lithium-ion battery are better. When the relationship between the first adhesive tape, the second adhesive tape and the area of the first material layer is adjusted to meet 0.3≤S≤6, the rate discharge capacity retention performance, room temperature cycle capacity retention performance, cycle thickness expansion performance and energy density of the lithium-ion battery are better. When the mass proportion of fluoroethylene carbonate in the electrolyte is adjusted to meet 2.2≤E≤13.5, especially 5.5≤E≤11.5, the rate discharge capacity retention performance, room temperature cycle capacity retention performance, cycle thickness expansion performance and energy density of the lithium-ion battery are better. When the mass proportion of lithium nitrate in the electrolyte is adjusted to meet 0.1≤F≤8.8, the rate discharge capacity retention performance, room temperature cycle capacity retention performance, cycle thickness expansion performance and energy density of the lithium-ion battery are better.
[0102] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A secondary battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The negative electrode plate comprises a first material layer, a second material layer and a negative electrode current collector; The first material layer includes silicon-based particles and first particles, wherein the first particles include at least four of lithium, lanthanum, aluminum, titanium, phosphorus or oxygen; The second material layer includes carbon-based particles and second particles, and the second particles include lithium, lanthanum, zirconium and oxygen; The second material layer is disposed between the negative electrode current collector and the first material layer.
2. The secondary battery according to claim 1, characterized in that: The circumscribed circle of the cross section of the silicon-based particle is a first circumscribed circle, and the diameter of the first circumscribed circle is R1 nm; A circular region that is concentric with the first circumscribed circle and has a radius of R1+500 nm is taken as the first region. The number of the first particles in the first region is M, and 10≤M≤119.
3. The secondary battery according to claim 1, characterized in that: The circumscribed circle of the cross section of the carbon-based particle is a second circumscribed circle, and the diameter of the second circumscribed circle is R2 nm; A circular region concentric with the second circumscribed circle and with a radius of R2+500 nm is taken as the second region. The number of the second particles in the second region is N, and 4≤N≤88, preferably 11≤N≤38.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: The secondary battery satisfies at least one of the following conditions: (1) The carbon-based particles include at least one of graphite or hard carbon; (2) The first particle includes Li 1+x Al x Ti 2-x (PO4)3 or Li x La (2-x) / 3 TiO3, where 0.1≤x≤0.3; (3) The second particles include Li7La3Zr2O2.
5. The secondary battery according to claim 1, characterized in that: Based on the mass of the first material layer, the mass proportion of titanium is T%, 2.12×10 -3 ≤T≤1.36, preferably 0.14≤T≤0.
54.
6. The secondary battery according to claim 1, characterized in that: Based on the mass of the first material layer, the mass proportion of silicon element is a%, the mass proportion of phosphorus element is b%, and the first material layer satisfies at least one of the following conditions: (1)5≤a≤98.6; (2)0.04≤b≤2.43; (3)2.06≤a / b≤2465.
7. The secondary battery according to claim 1, characterized in that: The thickness of the first material layer is H1 μm, the thickness of the second material layer is H2 μm, p=H1 / (H1+H2), 0.08≤p≤0.
86.
8. The secondary battery according to claim 1, characterized in that: The first material layer and the second material layer both include a binder; Based on the mass of the negative electrode plate, the mass proportion of the binder in the first material layer is K%, the mass proportion of the binder in the second material layer is J%, 0.55≤K / J≤25.6, preferably 1.5≤K / J≤16.
9. The secondary battery according to claim 1, characterized in that: The electrolyte includes fluoroethylene carbonate. Based on the mass of the electrolyte, the mass proportion of the fluoroethylene carbonate is E%, 2.2≤E≤13.5, and preferably 5.5≤E≤11.
5.
10. The secondary battery according to claim 9, characterized in that: The electrolyte includes lithium nitrate; Based on the mass of the electrolyte, the mass proportion of the lithium nitrate is F%, and 0.1≤F≤8.
8.
11. The secondary battery according to claim 1, characterized in that: The positive electrode sheet and the negative electrode sheet are both provided with a tab; the positive electrode sheet, the separator and the negative electrode sheet are sequentially stacked and wound to form an electrode assembly, with the thickness direction of the electrode assembly being the first direction; the negative electrode sheet is provided with a first adhesive tape and a second adhesive tape, and the positive electrode sheet is provided with a third adhesive tape; The first adhesive tape is disposed on at least a portion of the surface of the negative electrode tab, and the third adhesive tape is disposed on at least a portion of the surface of the positive electrode tab; The projection of the second adhesive tape along the first direction at least partially overlaps with the projection of the positive electrode tab along the first direction.
12. The secondary battery according to claim 11, characterized in that: The sum of the areas of the first adhesive tape and the second adhesive tape is S1 cm 2 , the area of the first material layer is S2 cm 2 ,S=100×S1 / S2,0.3≤S≤6。 13. The secondary battery according to claim 11, characterized in that: The capacitance-voltage characteristic curve of the negative electrode plate has reduction peaks at 0 to 0.8V, 1.5V to 1.8V and 2.3V to 2.5V respectively.
14. An electronic device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 13.
Citation Information
Patent Citations
Negative pole piece, electrochemical device comprising negative pole piece and electronic device comprising negative pole piece
CN115148960A
Secondary battery and electronic device
CN118367105A
Negative electrode and secondary battery
CN118661281A
Secondary battery, process for preparing same, and apparatus comprising secondary battery
US20220102708A1
Negative electrode plate, secondary battery, battery module, battery pack and electric device
WO2024007142A1